Electric linear dichroism transients of bent DNA fragments - Umazano, Juan Pablo (2013)
We study the effect of translational-rotational hydrodynamic coupling on the transient electric linear dichroism of DNA fragments in aqueous solution. As opposed to previous theoretical works, where analytic solutions valid in the limit of low electric field were reported, we present here a numerical approach which allows to obtain numerical results valid independently from the applied electric field strength. Numerical procedures here used are an extension to the transient-state of those developed in a previous work for the study of the problem in the steady-state. The molecular orientational processes induced by an electric field is characterized with statistical arguments solving the Fokker- Planck equation by means of the finite difference method to know the orientational distribution function of molecules.